Yi Shen Juan Bi Pill Ameliorates Bone Loss and Destruction Induced by Arthritis Through Modulating the Balance of Cytokines Released by Different Subpopulations of T Cells - Zhao, Hongyan; Xu, Huihui; Zuo, Zhengyun; Wang, Gui; Liu, Meijie; Guo, Minghui; Xiao, Cheng (Frontiers in Pharmacology, 2018)
The Yi Shen Juan Bi Pill (YSJB), a traditional Chinese compound herbal drug, has been used as an anti-rheumatic drug in clinical practice. Cartilage and bone destruction of inflamed joints is the hallmark of rheumatoid arthritis (RA). Our previous study suggested that YSJB had a protective effect on joint damage in collagen-induced (CIA) rats. However, the role and the mechanism of YSJB in inflammation-induced bone loss are unavailable. The current study aimed to further evaluate the effect of YSJB on the joint destruction and the systemic bone loss, and to clarify the potential mechanism. CIA model was generated by using collagen II and incomplete Freund's adjuvant in Sprague-Dawley rats. After 4 weeks treatment, arthritic index, tissue pathology, micro-computed tomography scanning (μ-CT), and bone mineral density (BMD) analysis were performed. YSJB decreased arthritic scores and bone destruction; improved the BMD of lumbar vertebrae and bone volume fraction of inflamed joints. Moreover, YSJB significantly decreased the production of serum bone resorption markers, including Tartrate-Resistant Acid Phosphatase (TRACP), N-terminal telopeptide of typeⅠcollagen and C-terminal telopeptide of typeⅠcollagen. Meanwhile, it increased the level of serum bone formation marker typeⅠcollagen N-terminal propeptide. These results revealed that YSJB ameliorated bone destruction and reduced bone loss induced by arthritis. We have previously showed that Tregs inhibited osteoclast differentiation and bone resorption in vitro. Furthermore, others suggested that abnormality of Th1, Th17 may contribute to bone destruction. Here, we showed YSJB significantly up-regulated the percentage of Tregs, while also down-regulated the percentage of Th1 and Th17 cells. Our findings provide the evidence that YSJB ameliorates the severity of disease and joint degradation, and reduces systemic bone loss induced by arthritis. We propose YSJB modulates the balance of T cell phenotype, which affects the activation and differentiation of osteoclasts.